ESCENOGRAFÓA DEL TEATRO ROMEA DE MURCIA DE 1862 A 1877 - Sanz Romero de Castellón, Mª Elisa (Imafronte, 1993)
This paper begins with a brief synthesis of the project of building of the new theatre. its first opening and the different names it was given till the present one of Teatro Romea. We mention the documents which are relevant ro the point. We also deal with the work of scene painters on the front curtain and scenery, and transcribe the inventaries and hiring contracts in which sets and scene furniture and fittings are detailed 60th generul and for particular plays. All these issues are referred to the period between the inuuguration of the theatre, in 1862, and the first big fire, in 1877.